The WTO Doha Trade Round : Unlocking the Negotiations and Beyond. (Policy Papers; Policy Paper ;, 2011)
This note provides an update on the status of Doha negotiations and an outlook on significant non-Doha trade issues that should be tackled in the near future. Section II investigates what has stalled progress on Doha since the IMF Executive Board was last briefed in October 2008 (World Bank and IMF, 2008). Section III illustrates that notable gains would come from a Doha conclusion, both from actual new market access and--perhaps more crucially--from the added trade security that Doha would bring. However, Section IV suggests that the time may now have come to devote more resources to discussing important non-Doha issues at the WTO. Section V concludes that the Fund should continue to support both a Doha conclusion as well as the important work on non-Doha issues.